Early Spinal Surgery Following Thoracolumbar Spinal Cord Injury: Process of Care From Trauma to Theater. Issue 10 (15th May 2017) - Agostinello, Jacqui; Battistuzzo, Camila R.; Skeers, Peta; Bernard, Stephen; Batchelor, Peter E.
Abstract : Study Design: A retrospective cohort study. Objective: The aims of this study were to (1) determine the timing of surgery for traumatic thoracolumbar spinal cord injury (TLSCI) between 2010 and 2014 and (2) identify major delays in the process of care from accident scene to surgery. Summary of Background Data: Early spinal surgery may promote neurological recovery and reduce acute complications after TLSCI; however, it is difficult to achieve due to logistical issues and the frequent presence of other nonlife-threatening injuries. Methods: Data were extracted from the medical records of 46 cases of acute traumatic TLSCI (AIS level T1–L1) aged between 15 and 70 years. Patients with life-threatening injuries, not requiring spinal surgery or with poor general health, were excluded. Results: The median time to surgery was 27 hours [interquartile range (IQR): 20–43 hours] and improved from 27 hours in 2010 to 22 hours in 2014. Cases admitted via a pre-surgical hospital had a longer median time to surgery than direct surgical hospital admissions (28 vs . 24 hours, respectively). The median time from completion of radiological investigations to surgery was 18 hours, suggesting that theater access and organization of a surgical team were the major factors contributing to surgical delay. Number of vertebral levels fractured (≥5) and upper thoracic level of injury (T1–8) were also found to be associated with surgical delay. Conclusion: Earlier spinal surgery in TLSCI would be facilitated by direct surgical hospital admission and improved access to the operating theater and surgical teams. Level of Evidence: 3